Assessing news coverage of the South African Legislative laws - Ndyondya, Kanyisa (Centre for Film and Media Studies, 2015)
This thesis attempts to examine the news coverage of South Africa’s legislative laws passed by the Parliament, by looking at the coverage of print media using qualitative content analysis. The thesis aims to understand the dominant messages being conveyed within the news texts and reader comments, specifically whose voice was represented, who was the intended audience and what the overall tone was. The researcher argues that taking editorial positions, the control of content and toning down of the issues is determined by journalists which they consider doing such as national interest. In this geo-political context of South Africa, the engagement of media in covering the issue of legislative laws places an important area of study. It is the media that reports events, responses, criticisms etc. in relation to the legislative laws, on the basis of which various actors and concerned people make their views about the event. As well, how reporting is done, shaped, framed; what sources have been used in news; what roles journalists play in the news coverage; and how ownership of media differs in news reporting and coverage very much reflects on whether or not and to what extent the newspapers respects legislative laws are interesting questions to be answered. This study is based on the case study of the coverage of New Age and The Times. Despite journalists being expected to serve the national interest of the state, differences can be observed in coverage, reporting and providing spaces to news and articles related to New Age and The Times. This hypothesis also supports the argument projected in the thesis that there are real ideological reasons why the media do not oppose the status quo, based on ideological lens grounded by the state and reporting system could rarely go against the establishments implying to the commitment to patriotism and to the nation which the government represents (Wicker, p. 19 cited in Malek and Wiegand).